Bilateral total knee arthroplasty: Simultaneous versus staging in the same or in twice hospitalization - Mardani-Kivi, Mohsen (J Clin Orthop Trauma, 2020)
BACKGROUND AND OBJECTIVE: Arthroplasty is the main treatment in patients with advanced knee osteoarthritis. In bilateral lesions, it is frequently performed in two simultaneous or separate surgical procedures. In this regard, the present study aimed to compare the results of knee arthroplasty in two joints simultaneously at two different times. METHOD: In general, all 40–70 years old patients in need of complete bilateral total knee arthroplasty (BTKA) were enrolled in this descriptive cross-sectional study during 2009–2016. They were included in three groups of BTKA as simultaneously (n = 272), staging in the same hospitalization (146), and staging in different hospitalizations (245). To assess the quantitative and qualitative function of the knees, patients’ knees were evaluated before the surgery, and one month, three months, and two years after the surgery using the Knee Society Score (KSS) and Western Ontario and McMaster Universities Arthritis Index (WOMAC). Finally, hospitalization time, anesthesia duration, and medical costs were compared between the three groups. RESULTS: Based on the results, knee function improved based on WOMAC and KSS scales in all groups after arthroplasty although no significant differences were observed between the three groups. Patients’ satisfaction in simultaneous BTKA was significantly higher compared to the other two groups (P = 0.013). Eventually, complications demonstrated no significant differences between the three groups except for pulmonary and cerebral embolism which were more prevalent in old patients with a high body mass index in the simultaneous BTKA group (P = 0.035 and P = 0.043, respectively). CONCLUSION: Overall, simultaneous BTKA is a useful approach for reducing costs while increasing patients’ function and satisfaction although it has certain complications such as embolism in older overweight patients.